Psychometric properties of the Fear of Death Scale (CL-FODS) in young Peruvian university students - Pérez Zavala, Jesús Milton (2023)
The purpose of the study was to evaluate the Collett-Lester Fear of Death Scale (CL-FODS) at psychometric properties. 448 university students participated [H: 174, M: 274, DE: 3.0, ME: 23.27]. In the confirmatory factor analysis, better values ​​were found in the bifactor model (χ²/gl = 2.54, CFI = .91, TLI = .90, SRMR = .051, RMSEA = .06, AIC = 33467.22, PUC =.78, ECV = .77, Omega H = .91). Likewise, it was found that the Scale presents a medium effect on convergent validity with Fear of Covid19 (r=.49). Besides, reliability was obtained in the general scale (ω=.96) and by dimensions (MPM ω=.87; MPPM ω=.91; MMO ω=.90; MPMO ω=.92). Subsequently, it was corroborated through measurement invariance that the construct does not show differences according to sex and age. Finally, it was concluded that the LC - FODS has good psychometric properties.